The DEVELOPMENT of COGNITIVE ASPECT of LEARNERS THROUGH TEACHER PERSONALITY - Nazar Al Masri (Madania: Jurnal Ilmu-Ilmu Keislaman, 2011)
This paper studies about how is the position of education  which should not merely develop intellectual aspect of learners but also other aspects such as ethics, aesthetics,   and social character of the learners. Moreover, affective aspect or personality of the learners has become the aim of education and it is the most important part in the process of education to which every teacher should pay more attention. Furthermore, every teacher has ability to influence his students. This influence could be from teacher personality reflected from his behavior on how he acts, says, walks, and many others. Therefore, the good model from the teacher is needed.